Layanan Infrastruktur Komputasi Multitenant dengan OpenStack di Lingkungan MaaS - Joan Ricard Panggabean; Agung Budi Prasetijo; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2017)
The growth of high-quality computing needs triggers the development of infrastructure that requires huge costs and resources. This research applied OpenStack in Metal as a Service (MaaS) environment to provide multitenant infrastructure services in the form of virtual machines (IaaS). The capacity of this IaaS system can be configured based on the needs of the computing resources (CPUs, memory, storage, and network interfaces). Users within the tenant can request infrastructure services as their needs without requiring human interaction with each service provider.